Pemenuhan Hak Pendidikan Anak Jalanan di Kota Batam : Tantangan Dalam Mewujudkan Sustainable Development Goals (SDGs) - Winsherly Tan (Supremasi Hukum: Jurnal Penelitian Hukum, 2020)
Sustainable Development Goals (SDGs) have the main goal of directing the development of education to the eighth goal. Normatively, Indonesia already has a set of regulations regulating the right to education for children. However, Indonesia is still faced with various problems regarding street children, including those faced by the Batam City government in fulfilling the right to education for street children. The purpose of this study is first, to analyze the effectiveness of fulfilling the right to education for street children in Batam City. Second, to analyze and deepen the constraints faced by Batam City in fulfilling the education rights of street children. In this research, Soerjono Soekanto's theory of legal effectiveness was used. The research method used in this research is juridical empirical. Based on the research results, it was found that the local government of Batam City has not been effective in fulfilling the right to education for street children with several obstacles such as low parental knowledge and low family economy of street children. Keywords: Keywords: Street Children; Right; Education